DETECTION OF PULMONARY FUNCTION ON ACTIVE SMOKERS WHOM REGULARY PLAY WIND INSTRUMENT “PUI-PUI” - Sri Wahyuni; Framita Rahman (Media Kesehatan Politeknik Kesehatan Makassar, 2019)
The method used to increase the lung capacity value is to practice using a wind instrument, one of which is the traditional Makassar wind instrument, the Pui-Pui. The purpose of this study was to look at the description of the lung capacity values of pui-pui wind instrument players in Makassar City. This research was conducted at the Pulmonary Polyclinic of Wahidin Sudirohusodo General Hospital with 27 smokers using a purposive sampling technique. Examination of lung capacity is carried out using a spirometry device by converting its value based on values based on Pneumobile Indonesia. The results of this study indicate that smokers who have been "Pui-Pui" blown music artists for more than 6 years have lung function: 24 people (89%) who have normal lung impression, 2 people (7.4%) mild obstruction, and 1 person (3.7) mild restriction. The conclusion is the occurrence of lung function disorders due to smoking is minimized by the habit of playing a wind instrument "Pui-Pui", so that this can be used as a medium of prevention or treatment to improve the lung function of those who have smoking habits.